Penggunaan Chromebook Bermuatan Game Edukasi untuk Meningkatkan Aktivitas dan Prestasi Belajar Matematika Siswa SD di Kabupaten Boyolali - Setiawan, Toni; Nasrudin, Fajar; Nur Hasanah, Fatmawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Learning achievement is an indicator of a student's success in learning. One of the factors causing low mathematics learning achievement is due to low activity in learning. One of the government's efforts to improve the quality of basic education is by using chromebooks in the Teaching and Learning Activities (KBM) process. The aims of this research are: 1) To find out and prove that the use of chromebooks containing educational games can improve Mathematics learning outcomes. 2) To find out and prove that the use of chromebooks containing educational games can increase student learning activities. This research used the classroom action method (PTK), with the subjects being 21 class III students at SD N 1 Tarubatang, Boyolali Regency, Central Java Province. The results of the research show: 1) Completeness of student learning outcomes in Mathematics increased, namely from Pre-Cycle 28.57% or 6 students out of 21 students, increased in Cycle I namely 57.14% or 12 students out of 21 students, then increased again in Cycle II, namely 80.95% or 17 out of 21 students. 2) Student learning activity in Mathematics increased from Pre-Cycle 38% or 8 out of 21 students actively studying, increased in Cycle I namely 71% or 15 out of 21 students actively studying, then increased again in Cycle II namely 90% or 19 of 21 students actively studying. 3) Class Action Research (PTK) was declared successful in Cycle II because it met the success indicators, including: (a) the indicator of success in student learning outcomes was getting a score ≥ 70 individually and the classical (class) average was 75% achieved in the cycle II with results of 81% > 75%; (b) the indicator of success in student learning activities is the number of active students ≥ 80% achieved in cycle II with results of 90% > 80%.